Use of an Immediate Provisional Implant to Support a Full-Arch Interim Restoration: A Clinical Report - Jae-Hoon Lee, DDS, MS;1 Val Frias, DDS, MS;2 (Journal of Prosthodontics, 2005)
The use of provisional implants as the sole or adjunct mean of stabilization for interim fixed partial dentures has gained popularity in implant prosthodontic treatment.